Thermal Accumulation and Phenology Shifts in Agroforestry Trees of Himachal Pradesh - Dogra, Karina; Jangra, Mohan Singh; Bhardwaj , Satish Kumar; Thakur , Komal (Indian Journal of Agroforestry, 2026)
The experiment was conducted during 2023-24 at 1200-1400m (Nauni) and 1400-1600m (Kandaghat) amsl to study the phenological stages and thermal indices of selected agroforestry trees. This study investigates the thermal accumulation and phenological shifts of agroforestry tree species, specifically Grewia optiva and Toona ciliata, in the mid-hills of Himachal Pradesh under changing climatic conditions. Conducted over two years at different altitude 1200-1400m amsl (Nauni) and 1400-1600m amsl (Kandaghat), the research monitored key climatic variables, including temperature, humidity and rainfall. The findings revealed significant variations in thermal accumulation across altitudes, with Grewia optiva and Toona ciliata accumulating the lowest growing degree days (GDD) at 1200-1400m amsl and the highest at 1400-1600m amsl. Notably, growth stages commenced earlier in 1200-1400m amsl by 5-6 days compared to 1400-1600m amsl, indicating warmer conditions in 1200-1400m amsl. The study highlighted critical impacts of climate change on phenological patterns and thermal responses of agroforestry species, emphasizing the need for adaptive management strategies to sustain productivity in these ecosystems amidst evolving climatic challenges.